Clinical characterization of a hypersensitivity mixed bacterial and fungal dermatitis in a translational model of porcine NASH - Felgendreff, Philipp; Lawrence, Josephine M.; Hosseiniasl, Seyed M.; Jacobs, Julie F.; Amiot, Bruce P.; Felgendreff, Lisa; Minshew, Anna; Sultan, Ahmer; Ahmadzada, Boyukkhanim; Rahe, Michael C.; Nyberg, Scott L. (Frontiers in Cellular and Infection Microbiology, 2024)
The development of animal models of chronic liver disease via diet modification is a promising avenue for translational research but can lead to unexpected side effects that impact model adoption. While these side effects are well characterized in rodent models of nonalcoholic steatohepatitis (NASH), limited knowledge of these effects exists for novel porcine models of NASH. To close this gap, the present study investigates the side effects of diet-based NASH induction in pigs, with a systematic analysis of the pathologic mechanisms underlying dermatitis development and evaluation of treatment approaches.Twelve pigs (10 large domestic pigs, 2 Goettingen minipigs) were fed a methionine-and choline-deficient, high-fat diet for 8 weeks to induce NASH. A retrospective review of each animal's clinical record was performed to identify the side effects of the diet. Following the identification of diet-associated dermatitis, severity was judged by using a novel gradation system that characterized the individual lesions and body regions resulting in a cumulative evaluation. In addition to this clinical assessment, the etiology of the dermatitis was investigated via histopathologic and microbiologic testing. Furthermore, the success of prophylactic and therapeutic treatment approaches was evaluated by considering dermatitis development and clinical course.All study animals demonstrated unexpected side effects of the methionine-and choline-deficient, high fat diet. In addition to marked dermatitis, study pigs showed impaired weight gain and developed steatorrhea and anemia. Based on the skin gradation system, five animals developed severe dermatitis, four animals moderate dermatitis, and three animals mild diet-associated dermatitis. Histological and microbiological evaluation of the affected skin showed signs of a hypersensitivity reaction with secondary infection by bacteria and fungi. The analysis showed that preemptive bathing extends the lesion-free duration by nearly 20 days. Furthermore, bathing in combination with a targeted antibiotic treatment represented a helpful treatment approach for diet-associated dermatitis.The provision of a methionine-and choline-deficient, high fat diet represents an effective approach for inducing NASH liver disease in pigs but predisposes study animals to multiple side effects. These side effects are universal to animals on study but can be adequately managed and do not represent a significant limitation of this model.